Brussels South Airport. - Rollin, Pierre-Olivier (Wien : Krinzinger Projekte Wien, 2005)
Alvim, Fernando ; Barry, Orla ; Berlanger, Marcel ; Bouschet, Gast ; Castro, Jota ; Dekyndt, Edith ; Denicolai, Simona ; Duyckaerts, Eric ; Everaert, Patrick ; Gaillard, Frédéric ; Geers, Kendell ; Van Lerberghe, Raphaël ; Moerman, Jean-Luc ; Paparella, Juan ; Plateus, Benoit ; Provoost, Ivo
biog., ind. tent. p. 21-31
Engels
Exhibition. Brussels South Airport. Krinzinger Projekte Wien, 20.05.2005 - 30.07.2005.
boek